2023
DOI: 10.3389/fimmu.2023.1137037
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and transcriptional impacts of Janus kinase and/or IFN-gamma inhibition in a mouse model of primary hemophagocytic lymphohistiocytosis

Abstract: BackgroundPrimary hemophagocytic lymphohistiocytosis (pHLH) is an inherited inflammatory syndrome driven by the exuberant activation of interferon-gamma (IFNg)-producing CD8 T cells. Towards this end, ruxolitinib treatment or IFNg neutralization (aIFNg) lessens immunopathology in a model of pHLH in which perforin-deficient mice (Prf1–/–) are infected with Lymphocytic Choriomeningitis virus (LCMV). However, neither agent completely eradicates inflammation. Two studies combining ruxolitinib with aIFNg report con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It is evident that neither IFN-γ blockade nor ruxolitinib monotherapy can lead to complete disease control in HLH. In recent studies, the combination of ruxolitinib and anti-IFN-γ antibody in pHLH animal models demonstrated inconsistent results with various dosage [ 7 9 ]. Clearly, there is ongoing debate about whether combining cytokine-targeting agents could have an additive effect in mitigating inflammation in HLH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that neither IFN-γ blockade nor ruxolitinib monotherapy can lead to complete disease control in HLH. In recent studies, the combination of ruxolitinib and anti-IFN-γ antibody in pHLH animal models demonstrated inconsistent results with various dosage [ 7 9 ]. Clearly, there is ongoing debate about whether combining cytokine-targeting agents could have an additive effect in mitigating inflammation in HLH.…”
mentioning
confidence: 99%
“…In the last three years, three animal studies investigating the combination of emapalumab and ruxolitinib have been published, but with differences in conclusions [ 7 9 ]. This study represents the first clinical application of ruxolitinib and emapalumab combination in HLH, which demonstrated improved response rate compared to ruxolitinib or emapalumab alone.…”
mentioning
confidence: 99%